Contextualization of Legal Protection of Intellectual Property in Micro Small and Medium Enterprises in Indonesia - Disemadi, Hari Sutra (LAW REFORM, 2022)
The growing number of Micro, Small and Medium Enterprises (MSMEs) has brought about big potential for the implementation of intellectual property protection. The management and the ability to create is an essential key to develop intellectual property. According to this issue, this study is aimed at investigating and analyzing the contextualization of legal protection of intellectual property in the development of MSMEs in Indonesia. Doctrinal legal research method was applied in this study.  This legal study emphasizes on the conception that law can be seen as a set of laws and regulations which are systematically arranged based on a certain hierarchical order.  The result of the study shows that MSMEs and intellectual property are two inseparable entities. One of the government efforts to develop MSMEs in Indonesia is by simplifying MSME regulation through the implementation of omnibus law in order to avoid overlapping of regulations which may lead to complicated bureaucracy. Another finding of this study is that basically the protection of intellectual property is considered highly important for the vendors of MSMEs. The implementation of legal protection for the vendors of MSMEs and their intellectual properties provides opportunity for the business owners to maximize the economic value of their intellectual property. Intellectual property rights can be collateral to obtain banking credit because intellectual property rights are admitted as property that its ownership can be handed over.